Development of food-grade oleogel via the aerogel-templated method: Oxidation stability, astaxanthin delivery and emulsifying application. (January 2023) - Zhao, Wanjun; Wei, Zihao; Xue, Changhu; Meng, Yuan
Abstract: Templates for the fabrication of food-grade oleogels were prepared by freeze-drying of whey protein isolate (WPI)–carboxymethyl chitosan (CMCS) heat-set hydrogels, and the effect of the concentration of CMCS on aerogel properties was explored. It was observed that both the oil adsorption capacity and oil binding capacity were significantly improved when the CMCS concentration was up to 0.75% (w/w). With the further increase of CMCS concentration, the oil absorption capacity decreased. Scanning electric microscopy images exhibited that the corresponding aerogel showed dense and uniform porous networks. Compared with bulk oil, WPI–CMCS aerogel gel showed excellent oxidation stability. In addition, the delivery efficiency of aerogel-based oleogels as nutraceutical delivery carriers for astaxanthin (AST) was assessed. The bioaccessibility of AST in WPI–CMCS oleogels was significantly higher than that of bulk oil. Finally, the emulsification of aerogel-based oleogels was tested by TSI and droplet size. In comparison with WPI oleogel, the WPI–CMCS oleogel exhibited better physical stability and smaller droplet size. This work indicates that the path of oil structuring is not limited to the selection of existing oleogelators. The construction of aerogel templates from various protein/polysaccharide for oil absorption is also a promising path. Graphical abstract: Image 1 Highlights: Oleogel could be prepared from whey protein isolate–carboxymethyl chitosan aerogel. Aerogel-based oleogels (AOs) exhibited superior oxidation stability. AOs could serve as efficacious vehicles for hydrophobic nutraceuticals. AOs improved the lipolysis rate and the bioaccessibility of astaxanthin. The prepared AO-based emulsion showed superior physical stability.